Acute neuromuscular and hormonal responses to 20 versus 40% velocity loss in males and females before and after 8 weeks of velocity‐loss resistance training. Issue 9 (17th August 2022) - Walker, Simon; Häkkinen, Keijo; Virtanen, Roosa; Mane, Shashank; Bachero‐Mena, Beatriz; Pareja‐Blanco, Fernando
Abstract : New Findings: What is the central question of this study? Do males and females differ in fatiguability during dynamic loadings, and what are the acute neuromuscular and hormonal responses to 20 versus 40% velocity‐loss resistance loadings? How does an 8‐week velocity‐loss resistance training period modify acute neuromuscular and hormonal responses in males and females? What is the main finding and its importance? Using resistance training methods that regulated the within‐set fatigue limit, males appeared to be more susceptible to fatigue than females before the training period. This between‐sex difference was diminished after training. The predominant mechanisms of fatigue from 20 and 40% velocity‐based resistance training appear to be within the musculature. Abstract: Scientific examination of velocity‐based resistance training (VBRT) has increased recently, but how males and females respond to different VBRT protocols or how these acute responses are modified after a period of training is unknown. Habitually resistance‐trained males and females followed either a 20 or 40% velocity‐loss programme for 8 weeks. Acute squat loading tests (five sets, 70% one‐repetition maximum load, 3 min rest) were performed before and after the training period. Tests of maximum neuromuscular performance and blood sampling were conducted before, within 10 min of completion (POST) and 24 h after each acute loading test. Testing included countermovement jump, resting femoral nerve electrical stimulation and bilateral isometric leg press. Blood samples were analysed for whole‐blood lactate, serum testosterone, cortisol, growth hormone and creatine kinase concentrations. Countermovement jump height, maximum isometric bilateral leg‐press force and the force from a 10 Hz doublet decreased in all groups at POST after 20 and 40% velocity loss. Only males showed reduced force from the 100 Hz doublet and voluntary force over 100 ms at POST before training. The 40% velocity loss led to increased blood lactate and growth hormone responses before training in both males and females. After training, more systematic and equivalent responses in force over 100 ms, force from a 100 Hz doublet and blood lactate were observed regardless of sex/VBRT protocol. Overall, acute responses were greater from 40% VBRT, and males were more susceptible to acute loss in force production capacity before the training period. These VBRT protocol‐ and sex‐related differences were diminished after training.